2011
DOI: 10.1021/la104410r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Sepiolite in Aqueous Gels by Using Methoxysilanes and Its Impact on the Nanofiber Dispersion Ability

Abstract: Surface modification reactions on needle-like sepiolite using alkyl and functional silanes have been carried out in the form of aqueous gels. In contrast with modifications in organic solvents, reactions in water make it possible to modify the surface of almost-individual sepiolite fibers and produce either a continuous coating or a nanotexturization of the sepiolite fiber surface, depending on the reaction conditions. This clean procedure substitutes advantageously organic solvent surface modifications and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…At the opposite, the implication of fibrous clay minerals for electroanalytical purposes is scarce, although many works in literature have been devoted to their chemical modification [24][25][26][27][28]. Depending on the nature of the clay mineral, the preparation of organic-inorganic clay-based composite materials, exploited as electrode material proceeds mainly by two processes: (1) the intercalation of organic molecules within layered clay minerals such as kaolinite [29][30][31][32] and montmorillonite [1,[33][34][35][36], and (2) the grafting of functionalized organic molecules onto the surface of clay minerals [6,[37][38][39][40]. This last approach is convenient for all types of clay minerals bearing hydroxyl groups (aluminol or silanol) in their structure since it leads to the irreversible binding of the organic molecule on the clay surface.…”
Section: Introductionmentioning
confidence: 99%
“…At the opposite, the implication of fibrous clay minerals for electroanalytical purposes is scarce, although many works in literature have been devoted to their chemical modification [24][25][26][27][28]. Depending on the nature of the clay mineral, the preparation of organic-inorganic clay-based composite materials, exploited as electrode material proceeds mainly by two processes: (1) the intercalation of organic molecules within layered clay minerals such as kaolinite [29][30][31][32] and montmorillonite [1,[33][34][35][36], and (2) the grafting of functionalized organic molecules onto the surface of clay minerals [6,[37][38][39][40]. This last approach is convenient for all types of clay minerals bearing hydroxyl groups (aluminol or silanol) in their structure since it leads to the irreversible binding of the organic molecule on the clay surface.…”
Section: Introductionmentioning
confidence: 99%
“…Further organic modification of sepiolite with MTMS nanotexturises the surface as shown in figure 1b). The nanotexturization consists on evenly dispersed spheres arising from the MTMS self-condensation onto the sepiolite surface (Tiemblo et al, 2011). This nanotexturization of the sepiolite surface enables a fine dispersion of the particles into the polymer matrix by one-step conventional melt extrusion processing.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, sepiolite bearing FeCo (SepFeCo) nanoparticles were organically modified with methyl trimethoxysilane (MTMS) following a previously reported procedure (García et al 2011). Basically, 3 g of FeCo sepiolite were dispersed in a solution of 16 mmol of MTMS in 72 mL of water by means of a lab dissolver (Dispermat® LC2) operating at 12000 rpm during 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The first one has been modified with a quaternary ammonium salt (S-QAS) and the second one with a silane (S-S). The process to obtain and modify these particles can be found elsewhere [29,35,40].…”
Section: Methodsmentioning
confidence: 99%
“…Sepiolites have been shown to be appropriate inorganic nanofillers for polymers because of their diameter dimensions at the nanoscale and the high aspect ratio of this fibrous clay. With the appropriate surface treatment these particles can be well dispersed in different types of polymers, including PMMA [28,29]. It has been reported that the addition of sepiolites can improve some properties of the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%